Micro ceramic fuel cells with multilayered yttrium-doped barium cerate and zirconate thin film electrolytes - Bae, Kiho; Jang, Dong Young; Jung, Ho Jean; Kim, Jun Woo; Son, Ji-Won; Shim, Joon Hyung (ELSEVIER SCIENCE BV, 2014)
Multi- and mono-layered thin film electrolytes based on BaCe0.9Y0.1O3-delta(BCY) and BaZr0.85Y0.15O3-delta (BZY) ceramics are fabricated by pulsed laser deposition (PLO) for use in micro-protonic ceramic fuel cells (micro-PCFCs), and their microstructure and fuel cell performances are investigated. Fully dense and well-crystallized BCY and BZY layers are identified in the multi- and mono-layered electrolytes, and are confirmed by microstructural analyses. Fuel cell and impedance measurements confirm that the bare BCY cells exhibit superior performance to samples with BZY capping; however, this capping does not offer any advantage in terms of operational stability. In contrast, the BCY-capped BZY cell performs better than the bare BZY cell, implying that BCY possesses more active surface kinetics. Anodic improvement is as important as cathodic modification for the intermediate-temperature operation of PCFCs. The BCY-capped BZY cell also demonstrates excellent stability, maintaining a good open circuit voltage for over 10 h. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: LOW-TEMPERATURE; CONDUCTING ELECTROLYTES; PROTON CONDUCTIVITY; HIGH-PERFORMANCE; IT-SOFCS; FABRICATION; ELECTRODES; STABILITY; MEMBRANES; OXIDES